Advanced Nanomaterials for the Diagnosis and Treatment of Renal Cell Carcinoma. Issue 2 (21st December 2022) - Ji, Chen; Li, Junru; Mei, Junyang; Su, Weiran; Dai, Huili; Li, Fengqin; Liu, Peifeng
Abstract : Renal cell carcinoma (RCC) is the most common type of kidney cancer. Owing to the high morbidity rate of RCC, there is an urgent need for intensive research on robust materials to diagnose and treat RCC. Nanomaterials have been developed largely in the last three decades because of their numerous advantages, such as high specific surface area, simple surface functionalization, rapid onset of therapeutic action, superior biological activity, and other unique physical–chemical characteristics. Herein, first, various types of nanomaterials used in RCC treatment are introduced, including inorganic nanomaterials, lipid nanomaterials, synthetic polymer nanomaterials, and natural nanomaterials. Second, the different diagnosis and therapeutic mechanisms of nanomaterials in the kidneys are reviewed and these advantages of nanomaterials are highlighted. Furthermore, nanomaterials are investigated for the preclinical and clinical detection and treatment of RCC. Finally, the challenges and outlook of various nanomaterials for RCC diagnostic and treatment are discussed. Abstract : A variety of nanomaterials have clinical application potential in the treatment and diagnosis of renal cell carcinoma (RCC), which can be divided into inorganic nanomaterials, lipid materials, synthetic polymer nanomaterials, and natural nanomaterials. Furthermore, high targeting, good biocompatibility, and stability are the current research directions of RCC‐related nanomaterials.